FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN PENERAPAN SAP BERBASIS AKRUAL DAN AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (STUDI EMPIRIS PADA PEMERINTAH DAERAH KABUPATEN DOMPU) - Ajhar .; Akram .; Endar Pituringsih (Jurnal Akuntansi Aktual, 2015)
The successful implementation of accrual-based GovernmentAccounting Standard is a veryimportant thing that will have an impact on performance accountability of government agencies, thenit is necessary for the identification of the factors that can support the successful implementation ofaccrual-based GovernmentAccounting Standard and accountability performance of government agen-cies. This study aims to provide empirical evidence that the human resources, internal control systemand information technology are all factors that affect the readiness of accrual-based Government Ac-counting Standard application and accountability performance of government agencies. This researchwas conducted at 37 working units Dompu. The population in this study is the scope of local govern-ment civil servants Dompu. The sampling technique used was disproportionate stratified random sam-pling. Analysis of the data used is Structural Equation Modeling (SEM) based variants or commonlycalled the soft modeling, using analytical tools Partial Least Square (PLS). The results showed that thehuman influence on the readiness of the implementation of accrual-based Governmet Accounting Stan-dards, Information Technology affect the readiness of the implementation of accrual-based GovernmetAccounting Standards, and Readiness application of accrual-based Governmet Accounting Standardsaffect the performance accountability of government agencies, while human resource has no effect onperformance accountability of government agencies, internal control system has no effect on perfor-mance accountability of government agencies, and Information Technology does not affect the perfor-mance accountability of government agencies.Keywords:government accounting standards, accrual basis, local government, financial statements,performance accountability of government agencies.